Strategies to Increase Employee Engagement and Job Satisfaction by Paying Attention to the Needs and Preferences of the Millennial Generation: Strategies to Increase Employee Engagement and Job Satisfaction by Paying Attention to the Needs and Preferences of the Millennial Generation - Yusuf, Muhammad (PENANOMICS: International Journal of Economics, 2024)
This research aims to explore effective strategies in increasing employee engagement and job satisfaction, with attention to the needs and preferences of the millennial generation. In the era of globalization and rapid technological development, the millennial generation has become the main component of the workforce. Therefore, understanding their characteristics and expectations is crucial to creating a productive and harmonious work environment. Method The research used in this research is the literature review method to collect and analyze data from various academic sources that are relevant to the research topic. The results of the research are (1) Using and implementing appropriate technology, companies can meet the expectations of the millennial generation, so they can improve employee engagement and job satisfaction millennial generation, (2) Companies that pay attention to work flexibility can be an effective strategy in increasing employee engagement and job satisfaction of the millennial generation in the workplace, (3) By providing meaning in work and contributing it can have a positive impact on increasing employee engagement and job satisfaction millennial employees, (4) For companies that pay greater attention to work-life balance as an effort to improve employee engagement and job satisfaction millennial employees, and (5) BAn open feedback force will improve communication and build trust, which will ultimately improve employee engagement and job satisfaction millennial employees.